Images of a First‐Order Spin‐Reorientation Phase Transition in a Metallic Kagome Ferromagnet. (12th July 2020) - Heritage, Kevin; Bryant, Ben; Fenner, Laura A.; Wills, Andrew S.; Aeppli, Gabriel; Soh, Yeong‐Ah
Abstract: First‐order phase transitions, where one phase replaces another by virtue of a simple crossing of free energies, are best known between solids, liquids, and vapors, but they also occur in a wide range of other contexts, including even elemental magnets. The key challenges are to establish whether a phase transition is indeed first order, and then to determine how the new phase emerges because this will determine thermodynamic and electronic properties. Here it is shown that both challenges are met for the spin reorientation transition in the topological metallic ferromagnet Fe3 Sn2 . The magnetometry and variable temperature magnetic force microscopy experiments reveal that, analogous to the liquid–gas transition in the temperature–pressure plane, this transition is centered on a first‐order line terminating in a critical end point in the field‐temperature plane. The nucleation and growth associated with the transition is directly imaged, indicating that the new phase emerges at the most convoluted magnetic domain walls for the high temperature phase and then moves to self‐organize at the domain centers of the high temperature phase. The dense domain patterns and phase coexistence imply a complex inhomogenous electronic structure, which can yield anomalous contributions to the electrical conductivity. Abstract : A metallic magnet imaged in exquisite detail shows that upon cooling, the new state emerges at the boundaries of the magnetic domains, characteristic of the high‐temperature state, then propagates to the center of the magnetic domains, and expands upon further cooling. The images demonstrate that both states coexist in a large temperature window, which is characteristic of discontinuous transformations.